Pengaruh Metode Cooperative Script dalam Meningkatkan Hafalan Kosakata Bahasa Arab Kelas VII MTs Al-Jauhar - Sugiat; Setiawan, Ahmad Hadi; Susanto, Asep Bambang (Program Studi Pendidikan Bahasa Arab, 2024)
The purpose of this research is to find out whether there is an effect of the cooperative script method on increasing students' Arabic vocabulary memorization in class VII Arabic subject. The questions in this study include